Biofertilizantes foliares ecológicos en el comportamiento vegetativo y rendimiento de Lactuca sativa L. Loreto - Vargas Rodriguez, Victor Alberto (2025)
In order to know the effect of foliar biofertilizers at different concentrations on the agronomic characteristics and yield of Lactuca sativa L., lettuce variety Grand Rapids. A completely randomized design was used with five treatments: Biof 40%, Lix H 40%, Biof 20%, Lix H 20%, and a control (Biof 0%), with four replicates each. Data were analyzed using analysis of variance, test was applied to determine differences between treatments. The results showed statistically significant differences (p < 0.000) in plant height, root length, plant width, number of leaves, and plant weight. The higher concentration treatments (Biof 40% and Lix H 40%) achieved the highest averages in all evaluated variables: plant height (26.49 cm and 25.81 cm), root length (13.17 cm and 12.42 cm), plant width (31.81 cm and 31.16 cm), number of leaves (15.85 and 15.68), and plant weight (167.23 g and 161.60 g). In conclusion, foliar biofertilizers at 40% concentration show a significant positive effect on the growth and yield of lettuce. These treatments stand out as an effective and sustainable alternative for improving vegetable production, promoting the optimal agronomic development of plants.